Life-threatening severe malarial anaemia. - English, M (2000)
Despite our improved understanding of the pathophysiology of severe malaria, major changes in clinical management have not been forthcoming. However, in the case of life-threatening severe malarial anaemia, preliminary evidence suggests that changes in current clinical practice rather than the introduction of novel interventions may improve child survival. This review argues that further research into the clinical physiology of this syndrome is required and could provide compelling evidence for changes in practice particularly with regard to blood transfusion. We focus on the syndrome of severe, symptomatic malarial anaemia associated with a metabolic acidosis which has a high fatality rate. However, it should be remembered that a far greater number of children without signs of life-threatening disease nonetheless experience significant morbidity from severe anaemia. Many of these less-severely ill children may also require blood transfusion. However, the mode and rationale for transfusion in this less-severely ill group is specifically not addressed. Indeed, the arguments presented should not be extrapolated to suggest a uniform approach to transfusion is warranted, the role of blood in the less-critically ill child with severe malaria anaemia being a further area that requires urgent research.